p73 expression in medulloblastoma: TAp73/DeltaNp73 transcript detection and possible association of p73alpha/DeltaNp73 immunoreactivity with survival - Zitterbart, Karel; Zavrelova, Iva; Kadlecova, Jitka; Spesna, Renata; Kratochvilova, Adela; Pavelka, Zdenek; Sterba, Jaroslav (Acta neuropathologica, 2007)
The human p73 protein is essential for normal morphogenesis and maintenance of neural tissue. Recently, several TP73 transcripts have been revealed in medulloblastoma (MB), the most common malignant brain tumor in children. Here, we performed immunohistochemical analysis on 29 MB specimens using anti-p73alpha and anti-DeltaNp73 antibodies. Real-time PCR quantification was performed to assess TAp73 and DeltaNp73 transcripts in a subset of 13 MB samples. Normal cerebellar tissues and RNA were used for comparison. Pilot clinical-pathological correlations were also provided. We report significant differences for TAp73 and DeltaNp73 mRNA expression between tumor tissues and reference (P = 0.013, P = 0.028). Immunohistochemically, 52 and 29% MB samples were positive for p73alpha and DeltaNp73, respectively. p73alpha expression was found to be in both the nucleus and cytoplasm, whereas DeltaNp73 was localized predominantly in the cytoplasm. In normal cerebellum, positive staining for p73alpha and DeltaNp73 was observed in the Purkinje cells of newborns, not adult samples, which supports the developmental role of TP73 during organogenesis of the human cerebellum. Survival analysis has shown negative relationship of DeltaNp73-immunoreactivity with overall survival (OS) and event free survival (EFS) (P = 0.026 and P = 0.127, respectively). For p73alpha-positive cases, the negative trend in OS (P = 0.149) and EFS (P = 0.216) was also apparent. Our results indicate the involvement of p73 protein in MB tumorigenesis and define TP73 as a potential prognostic and therapeutic target for medulloblastoma.
Keywords: Gene Expression Regulation, Neoplastic; nádorová transformace buněk; Protein Isoforms; RNA, Messenger; Brain Neoplasms; Male; retrospektivní studie; Child, Preschool; Survival Rate; DNA-Binding Proteins; nádory mozku; Adolescent; Brain; prognóza; Child; Tumor Suppressor Proteins; regulace genové exprese u nádorů; Cell Transformation, Neoplastic; dítě; Adult; dospělí; imunohistochemie; mužské pohlaví; DNA vazebné proteiny; jaderné proteiny; protein - isoformy; meduloblastom; nádorové supresorové proteiny; mladiství; předškolní dítě; lidé; ženské pohlaví; Immunohistochemistry; Biomarkers, Tumor; Humans; mozek; Prognosis; Retrospective Studies; Female; Nuclear Proteins; messenger RNA; nádorové biomarkery; míra přežití; Medulloblastoma